Strategies for Enhancing Food Safety-A Policy Appraisal in Punjab, Pakistan - Ghulam Mustafa Dogar; Shazia Yaqoob (Journal of Public Policy Practitioners, 2023)
Ensuring the security and safety of the food supply across Pakistan is a complex challenge that demands continual evaluation as well as robust policy responses. This policy paper outlines a comprehensive strategy to address the challenges to enhance food safety across the province of Punjab, Pakistan. In this regard, this research takes into account a number of factors, such as international cooperation, technological developments, regulatory frameworks, and stakeholder roles. It also explores the dynamic nature of food safety risks, highlighting the necessity for proactive and adaptable policies to counter new hazards. A complex web of interrelated factors, from farming and food processing methods to factors impacting food distribution and consumption, define the comprehensive landscape of food safety. Regulatory frameworks are essential for reducing risks at every stage of this spectrum. This paper assesses the efficacy of the regulatory body, that is, Punjab Food Authority, in ensuring the safety of the food through an examination of its inspection procedures. This also involves a review of the current working of this authority, aiming to identify gaps for future improvements.